DNA Damage Response Gene-Based Subtypes Associated With Clinical Outcomes in Early-Stage Lung Adenocarcinoma - Zhao, Yang; Qing, Bei; Xu, Chunwei; Zhao, Jing; Liao, Yuchen; Cui, Peng; Wang, Guoqiang; Cai, Shangli; Song, Yong; Cao, Liming; Duan, Jianchun (Frontiers in Molecular Biosciences, 2022)
DNA damage response (DDR) pathways play a crucial role in lung cancer. In this retrospective analysis, we aimed to develop a prognostic model and molecular subtype based on the expression profiles of DDR-related genes in early-stage lung adenocarcinoma (LUAD). A total of 1,785 lung adenocarcinoma samples from one RNA-Seq dataset of The Cancer Genome Atlas (TCGA) and 6 microarray datasets of Gene Expression Omnibus (GEO) were included in the analysis. In the TCGA dataset, a DNA damage response gene (DRG)-based signature consisting of 16 genes was constructed to predict the clinical outcomes of LUAD patients. Patients in the low DRG score group had better outcomes and lower genomic instability. Then the same 16 genes were used to develop a DRG based molecular subtypes in TCGA dataset to stratify early-stage LUAD into two subtypes (DRG1 and DRG2) which had significant differences in clinical outcomes. The Kappa test showed good consistency between molecular subtype and DRG (K=0.61, P<0.001). The DRG subtypes were significantly associated with prognosis in the 6 GEO datasets (Pooled estimates of hazard ratio, OS: 0.48 (0.41-0.57), P<0.01; DFS: 0.50 (0.41-0.62), P<0.01). Furthermore, patients in DRG2 group benefited more from adjuvant therapy than standard-of-care, which was not observed in DRG1 group. In summary, we constructed a DRG-based molecular subtype that had the potential to predict the prognosis of early-stage LUAD and guide the selection of adjuvant therapy for early-stage LUAD patients.